Mechanical properties of components of the bonding interface in different regions of radicular dentin surfaces - Suzuki, Thais Yumi Umeda [UNESP]; Gomes-Filho, Joao Eduardo [UNESP]; Gallego, Juno [UNESP]; Pavan, Sabrina; Santos, Paulo Henrique dos [UNESP]; Fraga Briso, Andre Luiz [UNESP] (Elsevier B.V., 2015)
Statement of problem: The mechanical properties of the adhesive materials used in intraradicular treatments could vary according to the interaction between the restorative material and dentin substrate. An evaluation of these properties is essential to determine the success of the luting procedures performed on glass-fiber posts. Purpose: The purpose of this study was to evaluate the mechanical properties of dentin adhesives, resin cements, and the dentin that underlies the bonding interface in different thirds of intraradicular dentin. Material and methods: Forty extracted, single-rooted human teeth were used in this study. After the endodontic treatment of the post spaces, the teeth were divided into 5 groups (n=8): Adper Single Bond 2 + RelyX ARC, Excite DSC + RelyX ARC, Adper SE Plus + RelyX ARC, RelyX Unicem, and Set. The hardness and elastic modulus values were measured at the adhesive interface in different thirds of the radicular dentin by using an ultramicrohardness tester. The data were subjected to 2-way ANOVA and the Fisher protected least significant difference test (alpha=.05). Results: In the underlying dentin, the highest Martens hardness values were found in the apical region for all groups; the exceptions were the groups with the self-etching adhesive. In the adhesive layer, the highest Martens hardness values were obtained for the Adper SE Plus + RelyX ARC group; further, no statistical differences were found among the different regions for this group. RelyX ARC had the lowest Martens hardness and elastic modulus values in the apical regions when used with Adper Single Bond 2 and Adper SE Plus. No differences were found in the Martens hardness and elastic modulus values for the self-adhesive resin cement in the regions investigated. Conclusion: The mechanical properties of adhesive materials and the underlying dentin are influenced by the interaction between the two as well as by the depth of the analyzed intraradicular area.